Designing ferromagnetism in Cu(II) complexes using an elusive near-orthogonal bridging mode of the pyrazole ring. (1st March 2019) - Roy, Manasi; Adhikary, Amit; Debnath, Tanay; Das, Abhijit Kumar; Mondal, Raju
Graphical abstract: We report herein a unique experimental realization of predicted ferromagnetic coupling for near orthogonal bridged pyrazole units, with corroborating theoretical Broken Symmetry-DFT calculations. Abstract: The syntheses, crystal structures, magnetic properties and DFT calculations of four Cu(II) complexes of the formula [{Cu(2, 2′-bpy)(HCPCA)}(H2 O)2 ]·3H2 O (1 ), [Cu(dmbp)(HCPCA)] (2 ), [Cu(phen)(HCPCA)]·H2 O (3 ) and [Cu(phen)(CPCA)]2 ·DMF (4 ) [H2 CPCA = 3-(3-carboxyphenyl)-1H-pyrazole-5-carboxylic acid, phen = 1, 10-phenanthroline] are reported here. Our main focus was to design ta ferromagnetic complex and therefore concentrated on the mononuclear and binuclear copper complexes3 and4 . In complex3 the pyrazole unit of the H2 CPCA ligand binds (as HCPCA-) in a monodentate fashion to form the mononuclear complex, and in complex4 the pyrazole unit of the H2 CPCA ligand binds (as CPCA 2− ) in a bidentate fashion to form a binuclear complex, creating a near orthogonal orientation between the two Cu(II) ions. Temperature dependent magnetic susceptibility measurements show the appearance of weak ferromagnetic interactions for complex4, whereas complex3 shows paramagnetic behavior. The results are in excellent agreement with theoretical Broken Symmetry-DFT calculations.